Instant Attraction: Immediate Action-Effect Bindings Occur for Both, Stimulus- and Goal-Driven Actions - Janczyk, Markus; Heinemann, Alexander; Pfister, Roland (Frontiers in Psychology, 2012)
Flexible behavior is only possible if contingencies between own actions and following environmental effects are acquired as quickly as possible; and recent findings indeed point toward an immediate formation of action-effect bindings already after a single coupling of an action and its effect. The present study explored whether these short-term bindings occur for both, stimulus- and goal-driven actions (“forced-choice actions” vs. “free-choice actions”). Two experiments confirmed that immediate action-effect bindings are formed for both types of actions and affect upcoming behavior. These findings support the view that action-effect binding is a ubiquitous phenomenon which occurs for any type of action.